Comparison of the variability of the annual rates of change in FEV1 determined from serial measurements of the pre- versus post-bronchodilator FEV1 over 5 years in mild to moderate COPD: Results of the lung health study - Tashkin Donald P; Wang He-Jing; Halpin David; Kleerup Eric C; Connett John; Li Ning; Elashoff Robert (Respiratory Research, 2012)
Abstract Background The impact of interventions on the progressive course of COPD is currently assessed by the slope of the annual decline in FEV1 determined from serial measurements of the post-, in preference to the pre-, bronchodilator FEV1. We therefore compared the yearly slope and the variability of the slope of the pre- versus the post-bronchodilator FEV1 in men and women with mild to moderate COPD who participated in the 5-year Lung Health Study (LHS). Methods Data were analyzed from 4484 of the 5887 LHS participants who had measurements of pre- and post-bronchodilator FEV1 at baseline (screening visit 2) and all five annual visits. The annual rate of decline in FEV1 (±SE) measured pre- and post-bronchodilator from the first to the fifth annual visit was estimated separately using a random coefficient model adjusted for relevant covariates. Analyses were performed separately within each of the three randomized intervention groups. In addition, individual rates of decline in pre- and post-bronchodilator FEV1 were also determined for each participant. Furthermore, sample sizes were estimated for determining the significance of differences in slopes of decline between different interventions using pre- versus post-bronchodilator measurements. Results Within each intervention group, mean adjusted and unadjusted slope estimates were slightly higher for the pre- than the post-bronchodilator FEV1 (range of differences 2.6-5.2 ml/yr) and the standard errors around these estimates were only minimally higher for the pre- versus the post-bronchodilator FEV1 (range 0.05-0.11 ml/yr). Conversely, the standard deviations of the mean FEV1 determined at each annual visit were consistently slightly higher (range of differences 0.011 to 0.035 L) for the post- compared to the pre-bronchodilator FEV1. Within each group, the proportion of individual participants with a statistically significant slope was similar (varying by only 1.4 to 2.7%) comparing the estimates from the pre- versus the post-bronchodilator FEV1. However, sample size estimates were slightly higher when the pre- compared to the post-bronchodilator value was used to determine the significance of specified differences in slopes between interventions. Conclusion Serial measurements of the pre-bronchodilator FEV1 are generally sufficient for comparing the impact of different interventions on the annual rate of change in FEV1.